Development of Interactive Mobile Learning Based on Problem-Based Learning for Computational Thinking Material in High School - Wahyu Nur Hidayat; Ellvina Pramitadewi Pramitadewi; Rahmana Ilmi Hakim; Fauziyatur Rohmah; Aldhy Sigma Lintang Pamungkas; Heri Cahyono; Moh. Asrori; Warsono Warsono; Dzulkifli Abdullah (Universitas Negeri Semarang, 2025)
This research was motivated by students’ low interest and motivation in learning computational thinking. Computational thinking material is still presented in the form of theory and is not based on case studies so that students find it difficult to understand its implementation in everyday life. This study aimed to develop KompuThink, a Problem-Based Learning (PBL)-based mobile learning application for computational thinking instruction. Research and Development using the ADDIE model, through the stages of analysis, design, development, implementation, and evaluation. The research subjects were 35 class X students of SMA Negeri 6 Malang who were taking informatics subjects. Data were collected using expert validation questionnaires and user testing instruments and analyzed using descriptive quantitative methods. The results showed that media expert validation yielded an average feasibility score of 88% and material expert validation yielded 86%, both categorized as very feasible. Classroom trials resulted in an average student acceptance score of 92.27%, also categorized as very feasible. The novelty of this study lies in the development and feasibility evaluation of a PBL-based mobile learning application that explicitly targets core computational thinking topics (searching, sorting, stack, and queue) within the Indonesian high school context, a combination that has been rarely addressed in previous studies. These findings indicate that KompuThink is a highly feasible and well-accepted interactive mobile learning medium for computational thinking and can serve as a reference for future research and development in informatics education technology.